Internalisasi Nilai-Nilai Etika Islam dalam Pendidikan Dasar di SD Muhammadiyah Sambon: Studi Analisis Aksiologi Filsafat Islam - Nuruddin, Nuruddin; Mujiburahman, Mujiburahman (Lembaga Yasin AlSys, 2025)
This study aims to explore the implementation of Islamic ethical value internalization in primary education at SD Muhammadiyah Sambon. The research is grounded in the importance of instilling Islamic character from an early age through structured and contextual approaches within the school environment. Utilizing a descriptive qualitative approach and the axiology framework of Islamic philosophy, the study examines teaching practices and school culture in fostering ethical values such as honesty, responsibility, discipline, and compassion. Data were collected through observation, document analysis, and interviews with three Islamic Education (PAI) teachers, and analyzed thematically. The findings reveal that value internalization is carried out through three main strategies: teacher role modeling, habituation in daily routines, and integration of values into subjects and school activities. These findings underscore the critical role of teachers as ethical models and school culture as an effective medium for shaping students’ Islamic character. This study contributes theoretically to the discourse on Islamic educational axiology and offers practical recommendations for primary schools in developing value-oriented learning systems.